2017
DOI: 10.1111/chd.12457
|View full text |Cite
|
Sign up to set email alerts
|

Angiographically detectable Thebesian veins are a dynamic and reversible finding in the setting of congenital heart disease

Abstract: Angiographically detectable Thebesian veins are a rare finding in patients with congenital heart disease and may represent global changes in the coronary circulation. This is the first report, adult or pediatric, to demonstrate that ThV dilation is a dynamic process capable of both progression and regression. The physiologic impact of these findings remains to be elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…4,7,10 Third, in the more recent clinical literature, the main mentions of Thebesian veins are related to accidental penetration of the subendocardium by inappropriate catheters during LV angiography 1,11 or in the context of rare accompanying defects. 3,12,13 Fourth, another modern experimental study on sheep hearts suggested that Thebesian foramina could be seen in both ventricular chambers. 2 By injecting India ink into each coronary artery in autopsied hearts, the investigator identified communications between the coronary arteries and cardiac chambers (arterioluminal vessels) and between the coronary veins and cardiac chambers (venoluminal vessels) in 16 of 36 hearts.…”
Section: Editorialmentioning
confidence: 99%
See 2 more Smart Citations
“…4,7,10 Third, in the more recent clinical literature, the main mentions of Thebesian veins are related to accidental penetration of the subendocardium by inappropriate catheters during LV angiography 1,11 or in the context of rare accompanying defects. 3,12,13 Fourth, another modern experimental study on sheep hearts suggested that Thebesian foramina could be seen in both ventricular chambers. 2 By injecting India ink into each coronary artery in autopsied hearts, the investigator identified communications between the coronary arteries and cardiac chambers (arterioluminal vessels) and between the coronary veins and cardiac chambers (venoluminal vessels) in 16 of 36 hearts.…”
Section: Editorialmentioning
confidence: 99%
“…9 Moreover, the clinical relevance of these malformations is trivial in the framework of the entire coronary circulation. The occasionally mentioned coronary steal attributed to preferential flow into cardiac cavities from nutrient branches 3,12,13 is probably an erroneous description, because Fig. 2 Original drawings of a heart from Thebesius' dissertation, 10 including a cadaveric left ventricle (left) cut in the sagittal plane (apical view).…”
Section: Editorialmentioning
confidence: 99%
See 1 more Smart Citation
“…Forgotten knowledge of the coronary-cameral connections and the rediscovery of their dynamic nature in development: The result of a misnomer, ambiguous use of nomenclature, and varied evaluation methods To the Editor, Tannous et al report a case series that utilizes a semiquantitative grading system for following children with congenital heart disease and connections between the coronary arteries and heart chambers as identified on coronary artery angiography. 1 However, the authors are not the first to demonstrate the dynamic nature of the coronary artery-cameral connections. 2,3 In addition, Sirker et al reported a case of coronary artery fistula that was initially grade zero and then progressed to a higher grade.…”
mentioning
confidence: 99%
“…5 Tannous et al astutely noted that there is a difference between the arterioluminal and venoluminal connections. 1 However, they mistakenly refer to both types of connections as "thebesian veins," and cite a reference that utilizes inaccurate nomenclature. 6 Thebesius did not study the arterioluminal connections, and the arterioluminal connections are not veins ( Figure 1).…”
mentioning
confidence: 99%